A new challenge for emerging markets: the need to develop an outward FDI policy - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
While virtually all countries have policies in place to attract FDI, the picture is very different for outward investment. Most developed countries have policies in place, but most emerging markets do not. This Perspective argues that, to remain competitive, governments of emerging markets must develop policies for outward FDI.
Keywords: 330